The Influence of Social Media Usage on Student Learning Productivity at Medan State University - Muhammad Zaky; Refisi Ainjerimen Telaumbanua; Arisandi Amanda Siregar; Rosinta Joito Siregar; Imelda Juniarti Munthe; Dionisius Sihombing; Mela Novita Rizki (Outline Journal of Education, 2025)
This study aims to analyze the effect of social media usage on the learning productivity of students at Medan State University. Social media, as an integral part of everyday life, has positive and negative potential in supporting or disrupting the learning process of students. This study uses a quantitative approach through a survey of 31 students with a simple linear regression analysis method. The results showed that the use of social media has a significant effect on learning productivity with a significance value of 0.000. The regression coefficient of 0.394 indicates that increasing the use of social media can increase learning productivity, but the impact depends on how it is used. Social media can support access to information, collaboration, and learning motivation, but it also risks causing distraction and procrastination if not used wisely. Therefore, students need to manage their time and use of social media effectively to maximize its benefits in academic activities.